Correlation between total water absorption and wet compressive strength of compressed stabilised peat bricks - Deboucha, S.; Hashim, Roslan (2011)
Housing is a great problem in today and future world, the most basic building material for infrastructure construction and houses is the usual bricks or blocks. Although there are approximately 2,500 000 hectares of peat soils in Malaysia, only a small portion of this as being utilised. In this study, peat soil was investigated in tandem with the production of lightweight bricks. Peat soil, sand, cement and hydrated lime mixtures were steam autoclaved under different test conditions to produce brick samples. The purpose for this study was undertaken on the production of compressed peat - siliceous sand, PFA, OPC cement and lime as solid bricks to solving the problems of housing and builds the construction economically and environmentally by utilising local materials. The compressive strength and water absorption of stabilised peat bricks obtained under 6 and 10 Mpa pressure are 5.48 and 7.10 Mpa; 4.75 and 2.6, respectively. Tests were also conducted to study correlation between wet compressive strength and water absorption; it was found negative values, increase in strength decreased water absorption and hardening of the bricks with time.